Heterotopic Ossification Following Arthroplasty for Femoral Neck Fracture. (21st July 2021) - Comeau-Gauthier, Marianne; Zura, Robert D.; Bzovsky, Sofia; Schemitsch, Emil H.; Axelrod, Daniel; Avram, Victoria; Manjoo, Ajay; Poolman, Rudolf W.; Frihagen, Frede; Heels-Ansdell, Diane; Bhandari, Mohit; Sprague, Sheila
Abstract : Background: Heterotopic ossification (HO) is a frequent complication following hip surgery. Using data from the Hip Fracture Evaluation with Alternatives of Total Hip Arthroplasty versus Hemiarthroplasty (HEALTH) trial, we aimed to (1) determine the prevalence of HO following total hip arthroplasty (THA) for femoral neck fracture in patients ≥50 years of age, (2) identify whether HO is associated with an increased risk of revision surgery within 24 months after the fracture, and (3) determine the impact of HO on functional outcomes. Methods: We performed a multivariable Cox regression analysis using revision surgery as the dependent variable and HO as the independent variable. We compared Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores between participants with and those without HO at 24 months. Results: Of 1, 441 participants in the study, 287 (19.9%) developed HO within 24 months. HO was not associated with subsequent revision surgery. Grade-III HO was associated with statistically significant and clinically relevant deterioration in the total WOMAC score, which was mainly related to the function component of the score, compared with grade I or II. Conclusions: The impact of grade-III HO on the functional outcomes and quality of life after THA for hip fracture is clinically important, and HO prophylaxis for selected high-risk patients may be appropriate. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.